Kompetensi Pengadilan Tindak Pidana Korupsi dan Pengadilan Tata Usaha Negara Terkait Penyalahgunaan Wewenang yang Mengakibatkan Kerugian Keuangan Negara - Hiras Afandy Silaban; Alvi Syahrin; Budiman Ginting; Muhammad Ekaputra (Universitas Sumatera Utara, 2019)
Abstract. The results of this study concluded that (1) abuse of authority in administrative law and criminal law occurred when the officers have the Authority (either by attribution, delegation or mandate) does not implement the authority in accordance with the goal gave the authority. In this case, the abuse of authority may result in financial loss to the State between administrative law and criminal law are affected by the intention (mens rea) with a result of the Act (actus reus); (2) Dualism between the authority of the courts of criminal acts of Corruption by The country's Courts in the event of abuse of authority which resulted in financial losses of the country caused by the similarity of the concept, the subject of the intended norm (normadressat) and the desired behavior or behavior that is not desired (normgedrag) between the abuse of authority; (3) a court which has competency against the abuse of power that resulted in financial losses of the State is the country's Administrative Court and the Court of criminal acts of corruption. In this case, the competence of the courts of The States have restrictions (retriksi) about a time where The State Court can receive, check and disconnected or no abuse Report after the Examination and APIP before the Court of a criminal offence of corruption began the process towards the matter. In the matter of the petition examination submitted at trial after the criminal offence of corruption starts, then the process in court The State Court process must wait for the criminal offence of corruption is completed. Keywords : corruption, abuse of authority